Patterns of Leaving Home in Western Culture during the Transition to Maturity and Independence - Hadiani Fitri (Budapest International Research and Critics University, 2022)
Humans are creatures who think and feel and will, then humans will continue to grow. In the period of human development will always pass through its own stages, namely from adulthood to old age and ends with death. After experiencing a long childhood and adolescence, an individual will experience a period where he has completed his growth and requires himself to be in society and with other adults. As an individual who is already an adult, his roles and responsibilities will get bigger and stronger, no longer depending on his parents economically, sociologically or psychologically. They feel challenged to prove themselves as independent adults.